TRANSFORMASI PEMBELAJARAN KEJURUAN MELALUI KURIKULUM MERDEKA: PERSPEKTIF MULTI-STAKEHOLDER DI BIDANG TEKNIK OTOMOTIF - Ramadhan, Gilang; Hidayat, Nuzul; Wagino, Wagino; Nanda, Iffarial (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: The implementation of the Independent Learning Curriculum in Vocational High Schools requires comprehensive evaluation from direct users' perspectives to identify effectiveness and improvement areas. This study aims to analyze teachers' and students' perceptions of the Independent Learning Curriculum on Light Vehicle Engine Maintenance (PMKR) subjects at SMKN 1 Padang. The study employed a quantitative approach with survey method and descriptive design. Research subjects were 2 PMKR subject teachers and 46 students of grade XI Light Vehicle Engineering Program, selected using total sampling for teachers and proportionate stratified random sampling for students. Research instruments consisted of validated questionnaires with 5-point Likert scale. Data analysis used descriptive statistics with mean score calculations and interpretation categorization. Research findings show: (1) teachers' perceptions of the Independent Learning Curriculum on PMKR subjects are in